Leukocyte telomere length and lung function: a mendelian randomization study in European population - Zhu, Shenyu; Zheng, Wenlong; Rao, Dingyu; Tang, Zhixian; Liao, Xinhui (Frontiers in Physiology, 2024)
The telomere has long been regarded as a dependable biomarker for cellular senescence. The lung function can reflect the function and status of the lungs. As individuals age beyond adulthood, there is a gradual decline in lung function. However, the existence of a associated between leukocyte telomere length (LTL) and lung function remains uncertain.A two-sample Mendelian randomization (MR) analysis was used. The Singlenucleotide polymorphisms (SNPs) of LTL from the genome-wide association (GWAS) study 2 were used as exposure instruments variable, and the lung function indicator including Forced expiratory volume in 1-second (FEV1), FEV1 Best measure, FEV1 predicted and Forced vital capacity (FVC) from the Neale Lab and MRC-IEU were used as outcomes. The associated between the exposures and outcomes was assessed using inverse-variance weighted (IVW), MR-Egger, and weighted median methods. Sensitivity analysis was conducted using Cochran's Q-test, MR-Egger intercept test, MR-PRESSO, leave-one-out analysis, and Steriger test.Results: Using the IVW method, a significant association was identified between genetically determined telomere length extension and enhanced lung function in FEV1, with ukb-a-336P=0.127, OR=1.028,95CI%=1.003-1.042) and ukb-b-19657 (P=7.26E-05, OR=1.051,95CI%=1.025-1.077),in FEV1 predicted, ukb-a-234 (P=0.013, OR=1.029,95CI%=1.003-1.042), ukb-b-8428 (P=0.001, OR=1.032,95CI%=1.012-1.052), in FEV1 best measure, ukb-a-231 (P=7.24E-05, OR=1.050,95CI%=1.025-1.075), ukb-b-11141 (P=1.40E-09, OR=1.067,95CI%=1.045-1.090).The sensitivity analysis did not reveal heterogeneity or horizontal pleiotropy.Meanwhile, the Steriger test results also indicate that the directionality between exposureand outcome is correct. Therefore, the results indicated robustness.There is a correlation between longer LTL and better lung function in the European dataset.